FeVO4 Nanopolyhedron Photoelectrodes for Stable and Efficient Water Splitting. Issue 14 (21st June 2021) - Chang, Sheng; Wang, Mingqi; Wang, Chong‐Chen; Fu, Xijun; Bi, Hao; Zeng, Qingyi
Abstract: Crystalline FeVO4 nanopolyhedron (FVO NPH) photoelectrodes are successfully prepared by using an in situ solid‐state transformation from hydrothermal FeOOH films via adding vanadium precursor and following thermal treatments. The FVO NPH photoelectrodes possess uniformly dispersed polyhedral nanocrystals that directly grow on the conductive substrate with tunable film thicknesses. The unique morphology enables an outstanding photo‐electrocatalytic performance, and the optimized FVO NPH photoelectrode, which was annealed at 550 °C for 4 h with a film thickness of ∼560 nm, exhibits excellent photocurrent densities of ∼0.47 and ∼0.68 mA cm −2 at 1.0 and 1.2 V vs. Ag/AgCl, respectively. After decorating CoPi co‐catalyst, FVO/CoPi shows a highly efficient water splitting performance with O2 and H2 evolution rates of 7.53 and 15.32 μmol cm −2  h −1, respectively, which are ∼1.88 and ∼1.80 times, respectively, of these of the FVO NPH. The proposed photoelectrodes also show excellently chemical and physical stabilities in solar water splitting. This is the first time reported the preparation of well‐organized nanostructured FeVO4 films, which warrants further optimization studies on morphologies and compositions of FeVO4 ‐based photoelectrodes. Abstract : The Ironing job V‐ell done : State‐of‐the‐art, crystalline FeVO4 nanopolyhedron photoelectrode for photo‐electrocatalytic water splitting was successfully prepared by using an in situ solid‐state transformation from hydrothermal FeOOH films via adding vanadium precursor and following thermal treatments.